PENGARUH PERAWATAN LUKA PERINEUM TERHADAP PERILAKU PERSONAL HYGIENE IBU POST PARTUM DI WILAYAH KERJA PUSKESMAS POREHU KABUPATEN KOLAKA UTARA - Astri Yuliandini; Suhartini; Ani (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2023)
skin and muscle that lies between the vagina and anus. Perineal tears can occur in almost all first births (primiparas). Objective: The purpose of this study was to determine whether there is an effect of perineal wound care on personal hygiene behavior. Design: This research method uses quantitative research with a cross sectional study approach. The population in this study were all postpartum mothers who were at the Porehu Health Center in North Kolaka Regency, as many as 74 respondents. The sampling technique was purposive sampling, namely taking respondents by limiting the criteria set with a total sample of 42 respondents. The research instrument used was a questionnaire for personal hygiene variables which had 10 question items using the gutmen scale and perineal wound care variables using SOP. Results: The results showed that of the 42 people who were used as samples, 29 people (69.0%) did perineal wound care and 13 people (31.0%) did not treat perineal wounds. 27 people (64.3%) had good behavior in personal hygiene and 15 people (35.7%) had less. Conclusion: The results showed that there was an effect of perineal wound care on personal hygiene behavior. Suggestion: It is hoped that midwives who work in the postpartum department will increase their attention in providing information about perineal wound care